(untitled) (Educación y Tecnología, 2023)
Education is a complex process that requires seeing it from multiple perspectives, one of which has to do with Information and Communication Technologies (ICT), the incursion of ICT in the higher education process has had many historical implications and development, in the particular case of the Universidad Veracruzana, its incursion, use and appropriation has taken on very important aspects in the educational development of the state of Veracruz, Mexico. But this process has a panorama of greater interest when it occurs in the field of the Bachelor of Pedagogy since it refers to the link of the career that seeks to shape future trainers and its link with ICT, hence it is necessary to understand its future .